A List of Novels for Teaching Business Ethics in the 21st Century. (September 2017) - Michaelson, Christopher
The use of stories in business ethics education is arguably as old as business ethics education. Recent advances in the psychology of stories show us how stories promote consideration of the human impact of business activity. While several books, journal articles, and other sources provide resource lists of novels and dramas for business ethics education, they tend to draw from a common well of material in the Western canon. Using criteria of length, quality, and relevance, this article provides a list of 12 recommended novels for business ethics education whose authors or characters resemble the diverse participants in 21st-century global capitalism, particularly women and emerging market actors.